Does the category house also include large (residential) buildings? - Dilparić, Branislava M. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
This paper reports a study whose aim was to determine whether / confirm that the category house also includes those buildings divided into (many) separate dwelling units and consisted of a (very large) number of storeys and whether / that they can also serve as a whole decomposed in the research on the house meronomy. The study was based on general dictionaries of the English language, picture dictionaries, dictionaries of architecture and building construction, as well as various non-dictionary sources dealing with houses, buildings, structures and/or offering examples of use of the lexeme house in its basic sense. The results of the study show that ‘house’ is indifferent to the observed physical features of the structures made for human habitation.